Knowledge towards diabetes mellitus among the Health Sciences and Education students in UiTM Selangor, Puncak Alam Campus / Mazura Bahari, Ayu Jonathan Seribu - Seribu, Ayu Jonathan; Bahari, Mazura (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Diabetes mellitus (DM) is a major emerging clinical and public health problem. It is essential to evaluate the knowledge of DM among students to help in designing a promotional strategy to plan an effective programme of health education among students in order to improve the knowledge on DM among young generation. The objective of this study is to evaluate the level of knowledge toward DM among students in UiTM Puncak Alam. A cross-sectional study was carried out among 376 students from March 2019 to June 2019, assessing their knowledge on diabetes, its symptoms, risk factor and complications. A Pearson chi-square and T-test was used to determine the level of knowledge. Out of 376 students, 72% were female and 27.9% were male with the mean age of 22 years. The study showed a significant difference in the level of knowledge between Health Sciences and Education students with (p-value <0.05). A higher mean total level of knowledge was observed among Health Sciences students (2.8, SD=0.32) compare to Education students (2.5, SD=0.52). Although there is the mean difference between the two faculties, this study showed that both students from Faculty of Health Sciences and Education have an excellent level of knowledge towards DM